(untitled) (Clinics, 2012)
OBJECTIVE: Bardet-Biedl syndrome is a genetic, multisystem disorder that causes severe visual impairment. This condition is characterized by retinal dystrophy, obesity, digit anomalies, renal disease, and hypogonadism. The purpose of this study was to analyze visual acuity and full-field electroretinogram findings in patients with the Bardet-Biedl syndrome phenotype. METHODS: The visual acuity of a group of 23 patients (15 males) with ages ranging from 6-36 years (mean = 15.8±6.4; median = 14.7) was assessed. Retinal function was evaluated by full-field electroretinography, and dark-adapted thresholds were assessed. RESULTS: Visual acuity in the better-seeing eye was 20/40 or better in 5 patients (21.7%), 20/50-20/150 in 13 (56.5%) patients, 20/200-20/400 in 2 (8.7%) patients and worse than 20/400 in one (4.3%) patient. The mean acuity in the better-seeing eye was 0.7±0.6 logMAR (20/100, Snellen equivalent). Scotopic rod and maximal responses were nondetectable in 21 (91.3%) patients, and cone responses were non-detectable in 15 (65.2%) patients. Elevated darkadapted visual thresholds were observed in all 19 patients who were able to be assessed, with 10 (52.6%) patients having thresholds greater than 30 dB. CONCLUSIONS: In a relatively young cohort of patients with Bardet-Biedl syndrome, only 21% had 20/40 or better vision. ERG scotopic responses were absent in the majority of cases, with cone responses being observed in less than half of cases. These findings showed the early deleterious effects in retinal function and visual acuity caused by this condition.